2021
DOI: 10.1038/s41598-021-81717-3
|View full text |Cite
|
Sign up to set email alerts
|

Resuscitation from hemorrhagic shock after traumatic brain injury with polymerized hemoglobin

Abstract: Traumatic brain injury (TBI) is often accompanied by hemorrhage, and treatment of hemorrhagic shock (HS) after TBI is particularly challenging because the two therapeutic treatment strategies for TBI and HS often conflict. Ischemia/reperfusion injury from HS resuscitation can be exaggerated by TBI-induced loss of autoregulation. In HS resuscitation, the goal is to restore lost blood volume, while in the treatment of TBI the priority is focused on maintenance of adequate cerebral perfusion pressure and avoidanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 38 publications
0
19
1
2
Order By: Relevance
“…With the exception of glucose, current findings also partially replicate a previous swine model of severe hemorrhage, which reported that increased glucose/potassium/lactate and decreased bicarbonate/MAP were associated with survival [ 15 ]. In contrast to previous work in rodents [ 20 ], EE-3-SO 4 administration did not significantly affect either point-of-care markers or MAP relative to Placebo, suggesting the need for polytherapeutic approaches to further promote survival and more rapidly restore homeostasis following TBI + HS [ 7 ].…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…With the exception of glucose, current findings also partially replicate a previous swine model of severe hemorrhage, which reported that increased glucose/potassium/lactate and decreased bicarbonate/MAP were associated with survival [ 15 ]. In contrast to previous work in rodents [ 20 ], EE-3-SO 4 administration did not significantly affect either point-of-care markers or MAP relative to Placebo, suggesting the need for polytherapeutic approaches to further promote survival and more rapidly restore homeostasis following TBI + HS [ 7 ].…”
Section: Discussioncontrasting
confidence: 91%
“…Hypovolemia also decreases arterial pressure and increases vasoconstriction, resulting in earlier and more severe cerebral dysautoregulation, reduced blood flow, hypoxia, increased contusion volume and a doubling of mortality rate in concurrent TBI + HS [ 5 , 6 ]. Although fluid resuscitation is recommended for HS, unless carefully managed it can also exacerbate brain edema and elevate intracranial pressure [ 7 ]. Similarly, hyperventilation helps to restore systemic acid–base balance following HS [ 8 ], whereas respiratory depression is the most common cause of death in preclinical models of moderate-to-severe TBI [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possible explanation for these findings is increased sympathetic tone with release of circulatory catecholamines. 46 Clinically, in patients with severe trauma with a class III or IV hemorrhage, use of exogenous catecholamines was associated with an alteration in levels of serum cytokines with significant increases in serum IL-10 and significant decreases in TNFα in the first 24 hours compared with patients with traumatic injury who did not receive catecholamines. 47…”
Section: Characterizing Reduced Systemic Immune Function After Tbi With Polytraumamentioning
confidence: 98%
“…Clinical outcomes after traumatic brain injury (TBI) are significantly worsened by concomitant hemorrhagic shock (HS) due to increased reduction of cerebral blood flow (CBF) leading to hypoxia, approximately doubling the mortality rate compared with TBI alone 1 3 . Despite advances in the management of TBI complicated by HS (TBI + HS), the current resuscitative approach to TBI + HS still entails immediate intravascular volume expansion, vasopressors, or oxygen supplementation 4 6 .…”
Section: Introductionmentioning
confidence: 99%